Amorphous Sb2S3 Anodes by Reactive Radio Frequency Magnetron Sputtering for High‐Performance Lithium‐Ion Half/Full Cells. Issue 11 (19th September 2019) - Wang, Qi; Lai, Yanqing; Liu, Fangyang; Jiang, Liangxing; Jia, Ming
Abstract : Herein, amorphous Sb2 S3 (a‐Sb2 S3 ) anodes are prepared on 3D conductive networks by a simple reactive radio frequency (RF) magnetron sputtering process, and their application feasibility in both a lithium half cell and LiFePO4 full cell is assessed. The a‐Sb2 S3 electrodes exhibit excellent cycling performance and rate capacity in the half cells, owing to the amorphous phase and 3D structure, and thus yield a high discharge capacity of 585.4 mAh g −1 at a current density of 0.2 C after 250 cycles. Moreover, the assembled a‐Sb2 S3 /LiFePO4 full cell can deliver 467.1 mAh g −1 at a high current density of 1000 mA g −1 even after 100 cycles. The prepared a‐Sb2 S3 shows great potential to be a promising alternative anode in the application of high‐electrochemical‐performance lithium‐ion batteries. Abstract : A novel 3D‐structured amorphous Sb2 S3 anode is designed to meet the requirements of energy/power density and long lifespan for future lithium‐ion batteries (LIBs). This anode shows excellent electrochemical performance in both the lithium half cell and LiFePO4 full cell due to its amorphous phase and 3D structure. The results indicate its potential application as an advanced anode for LIBs.